PENGARUH KONSERVATISME AKUNTANSI DAN TATA KELOLA PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Lailatus - Sa'adah; Adi - Prasetyo (Makro : Jurnal Manajemen Dan Kewirausahaan, 2021)
This study aims to: (1) determine whether the audit committee has an effect on tax avoidance. (2) to determine whether institutional ownership has an effect on tax avoidance. (3) to determine whether accounting conservatism affects tax avoidance. In this study the population is all coal companies listed on the Indonesia Stock Exchange (IDX) 2017-2018. Sampling using purposive sampling of 44 data, and the variables used are tax avoidance as an independent variable, while the audit committee, institutional ownership and conservatism accounting is the dependent variable. The analysis tool used multiple regression analysis. The test results prove that the audit committee and institutional ownership have a significant effect on tax avoidance, while accounting conservatism has no significant effect on tax avoidance.